1994
DOI: 10.1093/cvr/28.2.270
|View full text |Cite
|
Sign up to set email alerts
|

A1 Receptor mediated myocardial infarct size reduction by endogenous adenosine is exerted primarily during ischaemia

Abstract: While adenosine exerts its predominant modulation of infarct size during reperfusion, the cardioprotection mediated by A1 receptor mechanisms is modest and exerted principally during the ischaemic time period.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
67
2

Year Published

1996
1996
2008
2008

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 78 publications
(70 citation statements)
references
References 0 publications
1
67
2
Order By: Relevance
“…In our study, bradycardia was observed just after reperfusion in group CT, while KW3902 prevented bradycardia. Actually, previous report described that KW3902 has an effect against R-PIA-induced bradycardia (42). It is an effect of KW3902 against negative inotropic effect of A 1 receptors.…”
Section: Discussionmentioning
confidence: 93%
“…In our study, bradycardia was observed just after reperfusion in group CT, while KW3902 prevented bradycardia. Actually, previous report described that KW3902 has an effect against R-PIA-induced bradycardia (42). It is an effect of KW3902 against negative inotropic effect of A 1 receptors.…”
Section: Discussionmentioning
confidence: 93%
“…For example, protection with A 1 AR agonists is not always observed (197,225,312) and, as already noted, only a limited number of studies demonstrate exacerbation of ischemic injury with A 1 AR antagonism. Lasley and colleagues (162) have forwarded an intriguing hypothesis to explain some of the inconsistencies in A 1 AR-mediated responses.…”
Section: Adenosine Receptor-mediated Cardioprotection: Which Subtypesmentioning
confidence: 88%
“…Numerous subsequent investigations support A 1 AR agonist-mediated protection (75,80,136,181,182,207,210,267). Expression of A 1 ARs also confers ischemic tolerance in different models (64,197), and a relatively small number of studies document impaired tolerance with A 1 AR antagonists (225,312), supporting protection via endogenous adenosine. Signaling via the A 1 AR has been shown to provide protection not only in animal tissues but in the human myocardium (36,240).…”
Section: Adenosine Receptor-mediated Cardioprotection: Which Subtypesmentioning
confidence: 97%
See 2 more Smart Citations